A thermal test system for helmet cooling studies - Fitzgerald, S.; Atkins, H.; Leknys, R.; Kelso, R. (Proceedings, 2018)
One of the primary causes of discomfort to both irregular and elite cyclists is heat entrapment by a helmet resulting in overheating and excessive sweating of the head. To accurately assess the cooling effectiveness of bicycle helmets, a heated plastic thermal headform has been developed. The construction consists of a 3D-printed headform of low thermal conductivity with an internal layer of high thermal mass that is heated to a constant uniform temperature by an electrical heating element. Testing is conducted in a wind tunnel where the heater power remains constant and the resulting surface temperature distribution is directly measured by 36 K-type thermocouples embedded within the surface of the head in conjunction with a thermal imaging camera. Using this new test system, four bicycle helmets were studied in order to measure their cooling abilities and to identify `hot spots` where cooling performance is poor.